Adjustment of the reproductive activity of vulnerable lizard phymaturus williamsi at high altitudes - Castro, Susana Alejandra (2018)
In environments with cold climates, reproduction of lizards is restricted to short seasonal periods of activity, from mid-spring to early autumn. We studied the reproductive biology of Phymaturus williamsi (William’s Andean Lizard), a vulnerable and viviparous lizard from the palluma phylogenetic group of genus Phymaturus, endemic to rocky outcrops in cold environments in the Andes of San Juan, Argentina. We determined adult size, male and female reproductive cycles, litter size, mean annual reproductive output, and the relationship between gonadal cycles, fat bodies, and climatic variables. The shortest reproductive male and female were 87.2 mm and 86.4 mm SVL, respectively. The litter size per female was of one or two offspring every two years, and the mean annual reproductive output was 0.95 offspring/female/year. Births occurred from late summer to early autumn. Males exhibited an annual postnuptial cycle, with spermatogenesis beginning in mid-spring, spermiogenesis occurring in summer and autumn, and sperm stored during brumation through early spring when mating occurs. The male post-nuptial cycle is common in species of the patagonicus group, but not in the palluma group, as is P. williamsi. Nevertheless, the biennial female cycle is common in the palluma group, and results from the adjustment of the reproductive activity to the physiological and environmental constraints of the harsh and cold climatic conditions prevailing at high altitudes in the Andes. The knowledge of the reproductive traits of the vulnerable P. williamsi has direct relevance for the development of conservation strategies, as this information is fundamental for population viability analyses.